PARANOID SCHIZOPHRENIA -BETWEEN HYPERSEXUALITY AND SADOMASOCHISM - Trifu, Simona; Mihaela, Beligeanu; Ștefana, Iacob Beatrice; Parisa, Larimian Ștefania (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation/Background: In this paper we aimed at clinically analyzing a patient diagnosed with paranoid schizophrenia, who also displays features specific to multiple personality disorders, in the context of a presentation whose key topic is sexuality. Given the global prevalence and the severity of schizophrenia, it is increasingly important to appropriately adapt and identify the patients’ clinical and non-clinical personality profile. This paper also aims at making the profile of a patient diagnosed with axis I disorder ever since the age of 19, who also has got traits specific to certain personality disorders. At the same time, the work provides an interpretation of the behaviour from the psycho-dynamic point of view. Method: The following instruments were used for performing the analysis: a clinical interview, heteroanamnesis, psychological tests, clinical course monitoring, psychodynamic interpretations, defence mechanisms identification, psychiatric observation and treatment. Results: Based on the materials aforementioned, it has been established a possible diagnosis which includes multiple disorders: Antisocial Personality Disorder, Histrionic Personality Disorder, Schizotypal Personality Disorder, Obsessive Compulsive Personality Disorder, Cotard Syndrome, Kandinsky-Clérambault Syndrome. and there were identified defense mechanisms and coping strategies, under the influence of sexuality and sadomasochistic impulses. Conclusions: It is highlighted the clinical picture of a patient with paranoid schizophrenia, who presents symptoms for differential diagnoses, with disorganized discourse focused on sexuality, with delusional ideation, psychotic manifestation, but also with high suggestibility, especially on the paternal line